Um estudo sobre resoluções do problemas e modelagem matemática - Gonzaga, Mauro Fernandes Neves (2019)
This paper proposes to describe the development of Mathematical Modeling and Problem Solving as two main aspects of the research in Mathematics Education and its convergences in its methodological practices. From a bibliographical research we have made a historical approach to these research fields. In order to establish the consonances of these methodologies in teacher education, we collected data from the undergraduate courses of a faculty in the West zone of Rio de Janeiro, aiming to identify, implicitly or explicitly, approaches to Mathematical Modeling and Problem Solving in their curricular proposals. In the same institution, we applied a questionnaire about the impressions presented by the students regarding the concepts of the theoretical and methodological fields that are the object of this research. As a consequence of the questionnaire, we developed a booklet with conceptual, procedural and historical development approaches, seeking to highlight the gaps presented by the students in their answers to the research questionnaire.